2020
DOI: 10.3390/antiox9090852
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress: Concept and Some Practical Aspects

Abstract: Oxidative stress is defined as “an imbalance between oxidants and antioxidants in favor of the oxidants, leading to a disruption of redox signaling and control and/or molecular damage”. This Commentary presents basic features of this global concept which has attracted interest in biology and medicine. The term “antioxidants” in cellular defense against oxidants predominantly includes antioxidant enzymes with their substrates and coenzymes. Exogenous low-molecular-mass compounds also have a role, but this is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
147
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(224 citation statements)
references
References 45 publications
2
147
0
7
Order By: Relevance
“…As a natural byproduct of oxygen metabolism, ROS, such as hydrogen peroxide (H 2 O 2 ), hydroxyl radical (OH), and superoxide anion (O 2− ), plays an integral role in normal cell signaling and cellular function [ 68 , 69 ]. However, environmental stresses could increase ROS production via affecting or interrupting respiratory electron transport chains, enzymatic reaction, and other normal metabolisms [ 70 ], which could subsequently alter intracellular redox homeostasis and cause cellular oxidative stress [ 31 , 39 , 69 , 71 ]. To maintain the redox homeostasis within certain limits, the antioxidant enzymatic system is developed by aerobic organisms as the primary defense line for ROS scavenging, such as superoxide dismutase (SOD) and catalase (CAT) [ 2 , 69 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a natural byproduct of oxygen metabolism, ROS, such as hydrogen peroxide (H 2 O 2 ), hydroxyl radical (OH), and superoxide anion (O 2− ), plays an integral role in normal cell signaling and cellular function [ 68 , 69 ]. However, environmental stresses could increase ROS production via affecting or interrupting respiratory electron transport chains, enzymatic reaction, and other normal metabolisms [ 70 ], which could subsequently alter intracellular redox homeostasis and cause cellular oxidative stress [ 31 , 39 , 69 , 71 ]. To maintain the redox homeostasis within certain limits, the antioxidant enzymatic system is developed by aerobic organisms as the primary defense line for ROS scavenging, such as superoxide dismutase (SOD) and catalase (CAT) [ 2 , 69 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported that oil-derived PAHs could stimulate reactive oxygen species (ROS) production during their biotransformation, resulting in an elevation of ROS levels in marine organisms [ 2 , 29 , 30 ]. Overelevation of ROS levels could further induce oxidative damage of the biomacromolecules (including DNA, proteins, and lipids) [ 31 , 32 ], which is known as the primary mechanism involved in cell damage, apoptosis, and tissue injury in marine organisms exposed to oil-derived PAHs [ 29 , 33 , 34 , 35 , 36 ]. Additionally, numerous studies have documented that elevated temperature could cause physiological (e.g., increased oxygen consumption) and histological (e.g., tissue injury) changes in marine organisms, and it has been suggested that elevated temperature could also disturb the balance between endogenous and exogenous ROS levels and thereby cause an incapacity of the antioxidant defense system [ 23 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such situations do exist, e.g., in septicemia, ischemia/reperfusion and certain poisonings, and accordingly the term made a lot of sense. Over the years, the oxidative stress was repeatedly re-defined to consider new aspects of redox biology [ 346 , 347 , 348 , 349 , 350 , 351 ]. However, these modifications of the term were not always and not instantly accepted by the scientific community.…”
Section: Now the Language Problemmentioning
confidence: 99%
“…The redox-related stresses, thus, fused to a continuum that leaves no room whatsoever for unstressed normal life. In fact, physiological redox regulation, which is commonly not perceived as stressing, is now found under a broad stress umbrella as a form of eustress [ 351 ]. In short, the term stress has lost its power to differentiate between a pathological event, an adaptation to changing challenges and physiological fine-tuning of metabolic fluxes by redox regulation or redox signaling.…”
Section: Now the Language Problemmentioning
confidence: 99%
“…The concept of “oxidative stress” has been defined as “an imbalance between oxidants and antioxidants in favor of the oxidants, leading to a disruption of redox signaling and molecular damage” [ 4 ]. Urinary isoprostanes and 8-hydroxy-2′-deoxyguanosine (8-OHdG), among other body-oxidized compounds, are well-recognized biomarkers of oxidative stress, which have been found to be increased in several situations, including obesity, type 2 diabetes, and cardiovascular diseases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%